CHARACTERISTICS OF INORGANIC MARINE WASTE IN THE TANJUNG BUNGA AREA OF MAKASSAR CITY - Nuryana Nuryana; Fathuddin Fathuddin (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
Inorganic marine debris is a serious problem in coastal areas with high intensity of human activity. This study aims to characterize and measure the density of inorganic marine debris in the Tanjung Bunga area, Makassar City. Using a descriptive quantitative approach, the method applied was a 100 m line transect at three locations, namely station one residential area, station two gazebo area, and station three coastline. Data were collected in three repetitions covering the type, size and mass of debris, and supported by secondary oceanographic data (tides, currents, waves) from BMKG. The results showed that plastic was the most dominant type of debris (674 items), followed by wood (576), metal (354), styrofoam (202), rubber (170) and glass (94), with the largest mass recorded in plastic on the coastline, namely 10.95 kg. Based on size, macro debris dominated (61-67%), followed by meso (27-35%) and mega (4-6%). Oceanographic conditions reflect moderate-strong currents (19.2-43.6 cm/s), high waves between 0.28-0.40 meters, and a double daily tidal pattern, all of which influence waste distribution patterns. These findings confirm that plastic is a major threat to the coastal ecosystem in Tanjung Bunga (Jambeck et al., 2015; Suryawan, 2025), and serve as an important basis for formulating marine waste management policies and increasing public awareness.